Perbandingan genetic gain ikan nila pandu dan Nila kunti (Oreochromis niloticus) F4 Pada Pendederan I – III - Ainida, Alfi Nurul; Hastuti, Sri; Rejeki, Sri (Journal of Aquaculture Management and Technology, 2013)
The objectives of this research were to determine the genetic gain value of tilapia pandu and tilapia kunti F4 and to compare the growth between the best 10% (Top 10) tilapia pandu and tilapia kunti F4, also average tilapia pandu and tilapia kunti F4 fry (without selection). This study was done at Satker PBIAT (Central of Fresh Water Fish Culture Working Unit) Janti, Klaten from April – June. The top 10% of tilapia pandu and tilapia kunti F4, and the average tilapia pandu and tilapia kunti F4 (without selection) were used in this research. The fries were cultured in a 4x2x1 m3 net cages from nursery I –III. This research consisted of 4 treatments and 3 replication. Treatment A fry F4 top 10% tilapia and treatment B tilapia F4. Treatment C top 10% fry F4 kunti tilapia and treatment D fry tilapia kunti F4. The data collected were survival rate (SR), food convertion ratio (FCR), genetic gain, and water quality parameters. The data were analysed discriptively. tment B and D (average). In tilapia F4 got genetic gain in survival rate (SR) nursery I, II and III are 4.72%, 6.98%, 5.15%. Genetic gain values of weight nursery I, II and III are 47.23%, 51.35%, 63.37%. Genetic gain values of total length nursery I, II and III are 11.29%, 15.73%, 17.90%. Genetic gain FCR nursery I, II and III are 2.93%, 3.64%, 4.11%. While genetic gain obtained by kunti F4 survival rate (SR) nursery I, II and III are 6.35%, 5.40%, 7.20%. Genetic gain value of weight nursery I, II and III are 48.51%, 52.09%, 60.48%. Genetic gain value of total length nursery I, II and III are 8.77%, 13.29%, 24.54%. Genetic gain FCR nursery I, II and III are 3.44%, 3.79%, 4.14%. Water quality parameters during the research were still viable for the life of tilapia. Based on the results of this study concluded that individual selection program conducted in tilapia and tilapia kunti F4 could improve the performance of fish such as its survival, growth, and the food convertion ratio.